Pemanfaatan media aplikasi quizizz untuk meningkatkan hasil belajar siswa kelas v sekolah dasar pada pembelajaran ipa materi sistem reproduksi - Sefia khusnul khotimah; Yunita Laila Zulfa (STAI Syekh Jangkung, 2024)
Natural science are lessons that study the natural environment and the accompanying phenomena the human body system it self With the importance of science learning for future students lives. the role of teachers with perfect abilities is needed in providing science learning to students. So it is hoped that the final result will be that students can apply science learning in normal human life. This research aims to examine the influence of using Quizizz media in improving the learning outcomes of class VI students at elementary school at Jember Regency.. This research is in the form of quantitative research carried out using the classroom action research method which was carried out up to cycle II. The research results Indicated a rise in learning outcomes from pre-cycle to cycle I with a success percentage from 20% to 40%. Next, when cycle I was compared with cycle II, the completion percentage increased from 40% to 80%. So it was found from cycle II that there were 8 students who achieved the success percentage and there were 2 students who had not achieved the success percentage. In this research, Quizzizz media has an influence in the world of education so that the assessment or evaluation process in learning runs interactively and happily.